Novel system for distant assessment of cataract surgical quality in rural China. (13th May 2015) - Wang, Lanhua; Xu, Danping; Liu, Bin; Jin, Ling; Wang, Decai; He, Mingguang; Congdon, Nathan G; Huang, Wenyong
Abstract Background This study aims to assess the quality of various steps of manual small incision cataract surgery and predictors of quality, using video recordings. Design This paper applies a retrospective study. Participants Fifty‐two trainees participated in a hands‐on small incision cataract surgery training programme at rural Chinese hospitals. Methods Trainees provided one video each recorded by a tripod‐mounted digital recorder after completing a one‐week theoretical course and hands‐on training monitored by expert trainers. Videos were graded by two different experts, using a 4‐point scale developed by the International Council of Ophthalmology for each of 12 surgical steps and six global factors. Grades ranged from 2 (worst) to 5 (best), with a score of 0 if the step was performed by trainers. Main Outcome Measures Mean score for the performance of each cataract surgical step rated by trainers. Results Videos and data were available for 49/52 trainees (94.2%, median age 38 years, 16.3% women and 77.5% completing > 50 training cases). The majority (53.1%, 26/49) had performed ≤ 50 cataract surgeries prior to training. Kappa was 0.57∼0.98 for the steps (mean 0.85). Poorest‐rated steps were draping the surgical field (mean ± standard deviation = 3.27 ± 0.78), hydro‐dissection (3.88 ± 1.22) and wound closure (3.92 ± 1.03), and top‐rated steps were insertion of viscoelastic (4.96 ± 0.20) and anterior chamber entry (4.69 ± 0.74). In linear regression models, higher total score was associated with younger age (P = 0.015) and having performed >50 independent manual small incision cases (P = 0.039). Conclusions More training should be given to preoperative draping, which is poorly performed and crucial in preventing infection. Surgical experience improves ratings.